Diagnostic performance of MRI for assessment of response to neoadjuvant chemoradiotherapy in oesophageal cancer. Issue 5 (25th February 2019) - Vollenbrock, S. E.; Voncken, F. E. M.; van Dieren, J. M.; Lambregts, D. M. J.; Maas, M.; Meijer, G. J.; Goense, L.; Mook, S.; Hartemink, K. J.; Snaebjornsson, P.; ter Beek, L. C.; Verheij, M.; et al.
Abstract : Background: Patients with a pathological complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT) for oesophageal cancer may benefit from non‐surgical management. The aim of this study was to determine the diagnostic performance of visual response assessment of the primary tumour after nCRT on T2‐weighted (T2W) and diffusion‐weighted (DW) MRI. Methods: Patients with locally advanced oesophageal cancer who underwent T2W‐ and DW‐MRI (1·5 T) before and after nCRT in two hospitals, between July 2013 and September 2017, were included in this prospective study. Three radiologists evaluated T2W images retrospectively using a five‐point score for the assessment of residual tumour in a blinded manner and immediately rescored after adding DW‐MRI. Histopathology of the resection specimen was used as the reference standard; ypT0 represented a pCR. Sensitivity, specificity, area under the receiver operating characteristic (ROC) curve (AUC) and interobserver agreement were calculated. Results: Twelve of 51 patients (24 per cent) had a pCR. The sensitivity and specificity of T2W‐MRI for detection of residual tumour ranged from 90 to 100 and 8 to 25 per cent respectively. Respective values for T2W + DW‐MRI were 90–97 and 42–50 per cent. AUCs for the three readers were 0·65, 0·66 and 0·68 on T2W‐MRI, and 0·71, 0·70 and 0·70 on T2W + DW‐MRI ( P  = 0·441, P  = 0·611 and P  = 0·828 for readers 1, 2 and 3 respectively). The κ value for interobserver agreement improved from 0·24–0·55 on T2W‐MRI to 0·55–0·71 with DW‐MRI. Conclusion: Preoperative assessment of residual tumour on MRI after nCRT for oesophageal cancer is feasible with high sensitivity, reflecting a low chance of missing residual tumour. However, the specificity was low; this results in overstaging of complete responders as having residual tumour and, consequently, overtreatment. Abstract : Treatment of locally advanced oesophageal cancer consists of neoadjuvant chemoradiotherapy (nCRT) followed by surgery. In 25–30 per cent of these patients, the resection specimen shows a pathological complete response. This study shows that preoperative response assessment after nCRT performed visually on (diffusion‐weighted) MRI has promising overall diagnostic performance. To further increase the accuracy of response assessment, larger studies are needed, ideally using a multimodal approach combining (diffusion‐weighted) MRI with endoscopy/endoscopic ultrasonography and fluorodeoxyglucose PET/CT. T2W, T2‐weighted; DW, diffusion weighted. Not there yet